Using Functions for Easier Programming: Functional programming languages automate many of the details underlying specific operations. - Savage, Neil (Communications of the ACM, 2018)
The article discusses the use of functional programming languages to automate underlying operations. Topics include differences between object-oriented and functional programming languages, the use of functional programming languages to test ideas for programming, and the use of functional programming languages in financial services and cryptocurrency applications.